BUSINESS VALUE-ADDED APPROACH FOR TILAPIA FARMERS IN NAKHON PATHOM PROVINCE - ปุยสุวรรณ, ภัธรภร; ทิวถนอม, ธีรเดช (Thai Interdisciplinary and Sustainability Review, 2023)
The Article aimed to study the system of value-added for tilapia famers in Nakhon Pathom Province through value chain. Research model was mixed methods. Sampling was classified as instrument follows: group of consumer’s needs a total of 400 people group of farmer groups in Nakhon Pathom Province a total of 25 members and group of the Business Alliances and Public Sector a total of 12 people. The statistics was analyzed data, it consisted of frequency, percentage, arithmetic mean, standard deviation, and content analysis. Forums for opinion exchange as a data was surveyed consumer’s needs, semi-structured interviews, and in-depth interview. The finding revealed that: 1) Group of consumer’s needs was average marketing mix factors of sample population is at high level. 2) Potential terms of production capacity farmers in Nakhon Pathom Province and they won’t be able to be used. Due to this process was managed by middleman. 3) Research team and group of farmers in Nakhon Pathom worked together and brainstorm the processed of the fresh tilapia and designed product brand and packaging. It consisted of 3 products of tilapia such as Fresh tilapia products Tilapia products without fishbone and Tilapia product without fishbone. 4) To develop guidelines for marketing channel development and value-added business for tilapia famers in Nakhon Pathom Province through value chain as follows: online and offline marketing, and social network relations.